2012
DOI: 10.1158/1940-6207.capr-11-0420
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Suppresses Growth and Induces Apoptosis of Human Hepatocellular Carcinoma through the Modulation of STAT3/JAK2 Signaling Cascade In Vitro and In Vivo

Abstract: Cumulative evidences(s) have established that the constitutive activation of STAT3 plays a pivotal role in the proliferation, survival, metastasis, and angiogenesis and thus can contribute directly to the pathogenesis of hepatocellular carcinoma (HCC). Thus, novel agents that can inhibit STAT3 activation have potential for both prevention and treatment of HCCs. The effect of celastrol on STAT3 activation, associated protein kinases, STAT3-regulated gene products, cellular proliferation, and apoptosis was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 48 publications
1
92
0
Order By: Relevance
“…A study by Peng et al (15) demonstrated that celastrol arrested the human monocytic leukemia cell line U937 in G0/G1. Another study, by Rajendran et al (16), revealed that celastrol causes the accumulation of human hepatocellular carcinoma cells in the sub-G1 phase of the cell cycle. Furthermore, G2/M arrest has been identified in human cervical carcinoma and prostate cancer cells (15,17).…”
Section: Discussionmentioning
confidence: 97%
“…A study by Peng et al (15) demonstrated that celastrol arrested the human monocytic leukemia cell line U937 in G0/G1. Another study, by Rajendran et al (16), revealed that celastrol causes the accumulation of human hepatocellular carcinoma cells in the sub-G1 phase of the cell cycle. Furthermore, G2/M arrest has been identified in human cervical carcinoma and prostate cancer cells (15,17).…”
Section: Discussionmentioning
confidence: 97%
“…Natural agents, peptides, platinum compounds and other small molecules have been used to inhibit STAT3 activity in various tumor models including HCC [258]. Our group has identified number of STAT3 inhibitors including diosgenin, β-escin, γ-tocotrienol, butein, honokiol, and celastrol that can suppress growth and induce apoptosis in diverse HCC cell lines [259][260][261][262][263][264]. In addition, Chen and coworkers recently reported that a novel obatoclax derivative, SC-2001, can induce apoptosis in hepatocellular carcinoma cells through SHP-1-dependent STAT3 inactivation [265].…”
Section: Pharmacological Inhibition Of Stat3 Activation Pathway In Hccmentioning
confidence: 99%
“…To determine NF-kB and STAT3 activation, we conducted DNA-binding assay using TransAM NF-kB Kit or TransAM STAT3 Kit according to the manufacturer's instructions and as previously described (20,21). Briefly, 20 mg of nuclear proteins were added into a 96-well plate coated with an unlabeled oligonucleotide containing the consensus binding site for NF-kB (5 0 -GGGACTTTCC-3 0 ) or STAT3 (5 0 -TTCCCGGAA-3 0 ) and incubated for 1 hour.…”
Section: Dna-binding Assaymentioning
confidence: 99%